2017
DOI: 10.3892/etm.2017.4420
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates diabetic nephropathy in rats through negative regulation of the p38 MAPK/TGF-β1 pathway

Abstract: Resveratrol (RSV) has been shown to have a renoprotective effect against diabetic nephropathy, but the underlying mechanisms of this have not been fully elucidated. The aim of the current study was to explore the mechanisms responsible for the therapeutic effects of RSV in rat mesangial cells in vitro and in a rat model of diabetic nephropathy. The viability of CRL-2573 rat mesangial cells and their expression levels of p38, phosphorylated (p)-p38, transforming growth factor beta 1 (TGF-β1) and fibronectin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…Moreover, resveratrol showed protective effects on adipose tissue in diabetic mice by preventing ROS-mediated mitochondrial fission via AMPK-dependent upregulation of Drp1 phosphorylation, and by blocking the activation of NALP3 inflammasome via inhibition of endoplasmic reticulum stress (ERS) [93]. Resveratrol also protected against diabetic complications such as myocardial fibrosis, diabetic nephropathy, and erectile dysfunction [11,88,94]. Furthermore, maternal resveratrol administration to the rats was evidenced to prevent the offspring's glucose intolerance and islet dysfunction, which were associated with gestational diabetes [91].…”
Section: Diabetesmentioning
confidence: 99%
“…Moreover, resveratrol showed protective effects on adipose tissue in diabetic mice by preventing ROS-mediated mitochondrial fission via AMPK-dependent upregulation of Drp1 phosphorylation, and by blocking the activation of NALP3 inflammasome via inhibition of endoplasmic reticulum stress (ERS) [93]. Resveratrol also protected against diabetic complications such as myocardial fibrosis, diabetic nephropathy, and erectile dysfunction [11,88,94]. Furthermore, maternal resveratrol administration to the rats was evidenced to prevent the offspring's glucose intolerance and islet dysfunction, which were associated with gestational diabetes [91].…”
Section: Diabetesmentioning
confidence: 99%
“…In contrast, the STZ‐induced rats’ model is widely used to study the early changes in DN and characterized by severe hyperglycemia, hypoinsulinemia, and weight loss, possibly due to the increased catabolic effects of insulin deficiency, volume depletion, and osmotic diuresis (Kitada, Ogura, & Koya, ; Qiao, Gao, Wang, Wang, & Cui, ). In diabetic animal and individuals, the early clinical manifestations of the DN involve increased hyperfiltration, glomerular filtration rate (GFR), and microalbuminuria, whereas the end‐stage of the disease is characterized by severing glomerular damage, proteinuria, macroalbuminuria, oxidative stress, interstitial fibrosis, apoptosis, and impaired kidney function (Ding & Choi, ; Hayashi et al, ; Kitada et al, , ; Mima et al, ; Qiao et al, ; Reidy, Kang, Hostetter, & Susztak, ; Szrejder & Piwkowska, ; Yao, Zhang, & Chen, ).…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the mechanism of action is depicted in the provided graphical abstract ( Figure 8). (Kitada, Ogura, & Koya, 2016;Qiao, Gao, Wang, Wang, & Cui, 2017). In diabetic animal and individuals, the early clinical manifestations of the DN involve increased hyperfiltration, glomerular filtration rate (GFR), and microalbuminuria, whereas the end-stage of the disease is characterized by severing glomerular damage, proteinuria, macroalbuminuria, oxidative stress, interstitial fibrosis, apoptosis, and impaired kidney function (Ding & Choi, 2014;Hayashi et al, 2001;Kitada et al, 2003Kitada et al, , 2016Mima et al, 2008;Qiao et al, 2017;Reidy, Kang, Hostetter, & Susztak, 2014;Szrejder & Piwkowska, 2019;Yao, Zhang, & Chen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Kitada et al showed that, in diabetic db/db mice, RES treatment for 8 weeks (0.3% diet) resulted in decreased urinary albumin excretion [27]. Qiao et al showed that treatment of STZ-induced diabetic SD rats with RES (20 mg/kg/day) for 4 weeks resulted in reduced serum glucose and creatinine levels [28]. Consistent with these results, we observed that the serum urea and creatinine levels, as well as the urinary protein level, were obviously increased in a rat model of pregnant hypertension.…”
Section: Discussionmentioning
confidence: 99%